Perancangan Mesin Pengupas dan Pemarus Batang Ubi Kayu: Konsep Rancangan Mesin - Novel Karaman; Ndaru Adyono; Tria Puspa Sari; Luluk Edahwati; Wahyu Dwi Lestari Edahwati (BIOMEJ, 2021)
Indonesia is the fifth largest cassava-producing country, where the national cassava production per year reaches 23 million tons. On the other hand, the organic waste in the form of cassava stems with the potential to use a large alpha-cellulose stem content. Alpha-cellulose is a much-needed biomass material in the field of industry and renewable energy sources. Highquality alpha-cellulose is produced from cassava stem fibers that have separated the outer shell. Research in the design of machines capable of processing stripping and sequencing cassava stems simultaneously has the potential to increase the productivity of making Alpha-cellulose raw materials for industrial needs. The prototype design peeling machine and a cassava rod pucker using the engine element approach is expected to produce an engine design that has the specification of a 0.5 HP 3-phase main drive motor with a 1400 rpm rotation consisting of 2 pulley transmissions and a gearbox ratio of 60.